The Supply and Demand for Exports of Pakistan: The Polynomial Distributed Lag Model (PDL) Approach (The Pakistan Development Review, 2003)
In the global economy, the performance of any country will greatly depend on the performance of its exports. The trade performance determines the prospects of change. It helps countries win friends, and break the traditional mould of isolation and indifference. The performance of exports of countries depends on various price and non-price factors. In international trade transactions it is important to recognise that these transactions require some amount of time that occurs between the decision to buy and actual delivery of the product from foreign country. In the Econometric modelling lag occupies a central role. It is recognised that due to psychological, technical and institutional reasons, a dependent variable may respond to explanatory variables with lapse of time, in particular when dealing with time-series trade models.